PERTUMBUHAN TANAMAN KEDELAI (Glycine max L. Merr) PADA BERBAGAI INTERVAL PENYIRAMAN DAN TAKARAN PUPUK KANDANG - -, SARAWA; ARMA, MAKMUR JAYA; MATTOLA, MASKI (Jurnal Agroteknos, 2014)
The aims of the research were to study the interaction and the independent effects of irrigation frequency and manure on soybean vegetative growth. This research was arranged based on Completely Randomized Block Design in a factorial pattern, consisted of two factors. The first factor was irrigation frequency, consisted of four irrigation frequencies, i.e., 2, 4, 6, and 8 days. The second factor consisted of 3 manure dosages, i.e. without manure, 10 ton ha-1, and 20 ton ha-1. Each treatment was replicated 3 times, therefore, overall there were 36 experimental units. Data were analysed using analysis of variance. The variables observed were: plant height, stem diameter, number of leaves per plant, and leaf area. The result of the reasearch indicated that interaction between irrigation frequency and rate of manure did not affect the vegetative growth. Independent effect of irrigation frequency and rate of manure occured at plant height, stem diameter, number of leaves per plant, and leaf area per plant. The irrigation frequency of 2 days and manure 10 ton ha-1 significantly affected soybean vegatative growth. Keywords : Soybean, irrigation, manure